Reading in the Commandments of Arab Women in the Pre-Islamic Era" Marriage commandments as a model " - أمينة الحراحشة (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research deals with the literature of wills in the pre-Islamic era, and sheds light on the wills of Arab women in a study entitled: "A reading of the wills of Arab women in the pre-Islamic era". This study presented a set of commandments for Arab women in the pre-Islamic era trying to establish different relationships between the text, its author and its recipient, and then revealing the latent dimensions in the text such as psychological dimensions, social dimensions, intellectual dimensions and others, at the same time the study emphasizes the existing relationship between the word and meaning. Form and content, in a new vision that aims to activate modern critical methods in revealing the aesthetics of the literary text. The researcher tried to benefit from a non-methodological approach, such as stylistics, structuralism, or others, and also relied in her study a set of literary sources and references. Finally, the conclusion included the results of the study. Keywords: commandments, Arab women, pre-Islamic era.